Examining Polarization in Political Social Media: A Case of Twitter and the 2011 Canadian Federal Election - Gruzd, Anatoliy (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
The paper investigates whether or not political polarization exists in social media by using social networks analysis to analyze a sample of 1,492 users on Twitter.com, a popular microblogging platform, during the 2011 Canadian Federal Election.